Sharia Commercial Bank Financial Distress Prediction Through Financial Liquidity Ratio - Farohah, Anissa Nurul; Dahruji, Dahruji Dahruji (Universitas Siliwangi, 2023)
Introduction to the Problem: It is rarely found that liquidity ratio (Cash Ratio, Quick Ratio, and Current Ratio) are used as variable possible financialÂ distress at the Sharia General Bank in Indonesia.Purpose/Objective Study: The existence this study is aimed at predicting possibility of financial distress dominated by several liquidity ratios (Cash Ratio, Quick Ratio, and Current Ratio) at the Sharia General Bank in Indonesia. Researchers used logistics regression analysis research methodology.Findings: Total of 12 Sharia General Bank registered with Bank Indonesia and Financial Services Authority in period of 2018 the first quarter to 2021 the fourth quarter used as a research sample. The results were shown that Cash Ratio, Quick Ratio, and Current Ratio had no negative effect in financial distress.